Protocol to develop and pilot a primary mental healthcare intervention model to address the medium- to long-term Ebola associated psychological distress and psychosocial problems in Mubende District in Central Uganda (the Ebola+D project) - Leticia Kyohangirwe; Richard S. Mpango; Christine Tusiime; Rwamahe Rutakumwa; Joshua Ssebunnya; Andrew Obuku; Barbra Elsa Kiconco; Isaac Sekitoleko; Hafsa Sentongo; Kenneth Kalani; Wilson Muhwezi; Giulia Greco; et al. (PLoS ONE, 2025)
Ebola Virus Disease (EVD) presents significant global health challenges, including high mortality and substantial physical morbidity among patients and survivors. Beyond immediate health impacts, EVD survivors, frontline healthcare workers, and community members face profound mental health and psychosocial issues. Over 35 EVD outbreaks have occurred in Africa since 1976, often in the context of fragile health systems and chronic conflict, complicating the response to mental health needs. Uganda has experienced seven outbreaks, the latest from September 20, 2022, to January 11, 2023, affecting nine districts, with Mubende as the epicenter. The Mental Health Focus Area of the Medical Research Council/Uganda Virus Research Institute and London School of Hygiene and Tropical Medicine, Uganda Research Unit, in collaboration with Uganda’s Ministry of Health, has initiated the development and piloting of the Ebola+D mental health intervention to address the medium- and long-term mental health consequences of Ebola in the Mubende district. This intervention will be a collaborative stepped care model based on the successful HIV + D intervention in Uganda and the MANAS intervention in India. Participatory, theory-informed approaches will be employed in Mubende district to develop the Ebola+D mental health intervention. This will involve five phases: i) adaptation of the HIV + D collaborative stepped care mental health intervention into primary health care in Mubende district to produce the Ebola+D mental health intervention; ii) adaptation and translation of the Problem Solving Therapy for Primary Care (PST-PC) treatment manual to the local rural situation in Mubende district; iii) a pilot study to evaluate the acceptability, feasibility and impact of the Ebola+D mental health intervention on mental health outcomes; iv) a health economics component to examine the costs of the Ebola + D mental health intervention; and v) a qualitative component to explore the Ebola virus disease (EVD) associated negative beliefs and lived out experiences of affected members of the community. The findings from this study will inform future mental health and psychosocial interventions secondary to outbreaks of Emerging Viral Diseases (such as EVD) in low resourced settings such those in sub-Saharan Africa. Trial registration ClinicalTrials.gov NCT06093646